2022
DOI: 10.7150/thno.68667
|View full text |Cite
|
Sign up to set email alerts
|

Surface-engineered extracellular vesicles for targeted delivery of therapeutic RNAs and peptides for cancer therapy

Abstract: The advent of novel therapeutics in recent years has urged the need for a safe, non-immunogenic drug delivery vector capable of delivering therapeutic payloads specifically to diseased cells, thereby increasing therapeutic efficacy and reducing side effects. Extracellular vesicles (EVs) have garnered attention in recent years as a potentially ideal vector for drug delivery, taking into account their intrinsic ability to transfer bioactive cargo to recipient cells and their biocompatible nature. However, natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Based on the analyzed research and our observations [ 14 , 30 , 166 , 167 ], it must be noted that both small and large EVs are the future of personalized medicine, including not only in the diagnosis and prognosis of cancer patients but also as a treatment strategy. Such an application of our knowledge of exosomes can rely on two potential activities: (1) inhibiting the release of exosomes [ 168 ] and (2) using exosomes as a platform for chemotherapeutic agent transport [ 169 , 170 ] and as a ‘freighter’ for therapeutic RNAs and peptides [ 171 ]. Here, advanced techniques of biomedical engineering come to our aid [ 172 , 173 , 174 , 175 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analyzed research and our observations [ 14 , 30 , 166 , 167 ], it must be noted that both small and large EVs are the future of personalized medicine, including not only in the diagnosis and prognosis of cancer patients but also as a treatment strategy. Such an application of our knowledge of exosomes can rely on two potential activities: (1) inhibiting the release of exosomes [ 168 ] and (2) using exosomes as a platform for chemotherapeutic agent transport [ 169 , 170 ] and as a ‘freighter’ for therapeutic RNAs and peptides [ 171 ]. Here, advanced techniques of biomedical engineering come to our aid [ 172 , 173 , 174 , 175 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possessing a nanosized dimension and a favorable safety profile, RBCEVs represent a promising therapeutic delivery platform (Table ). With a continued growing interest in generating an efficient and versatile DDS, our group has developed a robust delivery platform using RBCEVs for chemotherapy drugs and RNA drugs in various cancer models. − ,, We have demonstrated that treatment with RBCEVs loaded with antisense oligonucleotides (ASOs) against the oncogenic miR-125b leads to inhibition of tumor growth with minimal toxicity in leukemic and breast cancer models . Taking advantage of the natural accumulation of RBCEVs in the liver, Zhang et al loaded RBCEVs with ASOs of microRNA-155 to decrease inflammation and ameliorate acute liver failure in a mouse model .…”
Section: Red Blood Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…This engineering approach is biocompatible and site-specific while maintaining a high copy number of engineered molecules per EV. Since then, many studies have expanded on this approach via the use of cyclic bifunctional peptides with higher copy number and the use of avidin–biotin interactions to conjugate larger proteins on the EV surface efficiently. ,, These studies have demonstrated that enzymatic ligation mediated by OaAEP1 C247A ligase is stable, irreversible, and does not alter the biocompatibility or physicochemical characteristics of the EVs.…”
Section: Red Blood Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…In 2022, Jayasinghe and co-workers conjugated RBCEVs with several peptides and/or antibodies for targeted delivery of cargoes to cancer cells [ 200 ]. They conjugated RBCEVs with a cyclic peptide to specifically target CXCR4 or with a monoclonal antibody anti-CD33 to promote the specific binding and uptake of the conjugated EVs by leukemia cells expressing the corresponding receptors.…”
Section: Rbc-derived Extracellular Vesicles (Rbcevs): Biogenesis and ...mentioning
confidence: 99%
“…CXCR4-conjugated RBCEVs were loaded with the pro-apoptotic peptide KLA, demonstrating that these were able to significantly suppress leukemia burden and increase survival in a leukemia xenografted mouse model. Antibody-conjugated RBCEVs were also used to deliver RNA antisense oligonucleotides to knock down FLT3 and miR-125b in cell lines and in patient-derived xenograft models of leukemia [ 200 ]. This study demonstrated for the first time that peptide/antibody-conjugated RBCEVs are biocompatible and non-immunogenic and can be used for targeted delivery of therapeutic peptides and RNAs for potential clinical applications.…”
Section: Rbc-derived Extracellular Vesicles (Rbcevs): Biogenesis and ...mentioning
confidence: 99%